(untitled) (Journal of Governance and Development (JGD), 2014)
The main objective of this paper is to empirically investigate the contribution of FDI to Poverty Reduction in Nigeria, covering the period 1980-2010. Data on GDP by Income and Life Expectancy (proxy for poverty level), FDI, Agricultural Output and Government Expenditure: Health, Education, and Agriculture were used as variables in GDP by Income and Life Expectancy model respectively in this study. The study employed ADF and PP unit root tests, residual unit root test of co-integration and the error correction modelling methodology. Based on the data analysis of the two models, it was discovered that foreign direct investment has a positive significant impact on poverty reduction in Nigeria. It was recommended that for Nigeria to attract the desired level of FDI that will stimulate poverty reduction, it must introduce sound economic policies and make the country investor-friendly coupled with political stability, sound economic management and well developed infrastructure.